Impacts of Along-Strait Winds on Sea Level, Sea Surface Temperature, and Current in the Jeju Strait During Summer 2022 - Shin, Chang-Woong; Min, Hong Sik; Lee, Seok; Oh, Kyung-Hee; Kim, Yong Sun; Kang, Hyoun-Woo; Choi, Byoung-Ju (Ocean science journal, 2025)
The along-strait wind in the Jeju Strait (JS) significantly impacts the sea level, surface temperature, and currents on its northern and southern coasts. During the summer of 2022, the winds in the JS were characterized by strong easterly winds that occurred before the approach of several typhoons. A strong correlation of 0.61 was found between the along-strait wind and the difference in sea level anomaly between the strait’s south and north coasts. A more robust correlation of 0.71 was estimated between the along-strait wind and the difference in sea surface temperature anomaly. When the positive (eastward) wind blows along the strait, it causes upwelling along the north coast, resulting in cold anomalies there and warm anomalies along the south coast, and vice versa. In addition, a positive correlation ( r = 0.39–0.50) was estimated between the along-strait wind and along-strait surface current, with a negative correlation ( r = −0.68 to −0.44) for the cross-strait current in most observation stations of the JS, except near the coast of Jeju Island. The positive along-strait wind causes the sea level to fall on the north coast and strengthens the eastward surface current. In contrast, the negative (westward) along-strait wind has the opposite effect, causing the sea level to rise near Wando, then slowing down or reversing the eastward surface current. Overall, these findings show that Ekman dynamics can explain wind-induced coastal upwelling and downwelling on both coasts of the JS, providing valuable insights into the environmental conditions surrounding marine organisms in this coastal region.